Patient adherence to pharmaceutical care amid the economic crisis in Greece: Underlying priority areas for policy makers. Issue 9 (September 2020) - Monokroussou, Maria; Siati, Georgia; Theodorou, Mamas; Siskou, Olga
Highlights: Patients facing financial difficulties were less likely to adhere to medication. 94.5 % of patients were able to buy the prescribed medication. 12 % of patients reduced their medication dosages. 71 % of patients remembered to take their prescribed medications daily. Almost 70 % of patients mentioned that using generics enables adherence Abstract: The purpose of the study was to investigate the degree to which chronic patients adhered to medication regimens during the economic crisis in Greece. It is a quantitative cross-sectional study, with a convenience sample of 1, 009 residents of Western and Northern Greece, aged ≥ 18 years, with chronic health problems. The survey was conducted between February and June 2016. Data were collected via a structured questionnaire with closed-ended questions, filled out during face to face interviews with all participants. The vast majority of respondents (94.5 %) said that they were able to buy prescribed drugs but had to economise in other ways (for example, by cutting back on clothing and travel) to cope with essential household expenses, including medication. Only 71 % of participants said they remembered to take their prescribed medications every day, following all of their physicians' recommendations. Almost 70 % of participants said that using generic medications made it easier to adhere to their treatment regimens. The results of a correlation analysis showed that patients experiencing financial hardships as a result of health problems were less likely to adhere to pharmaceutical care regiments than those who were not experiencing financial difficulties (p = 0.026). Men had a higher level of adherence than women (p = 0.001).